Prevención de los embarazos precoces en las alumnas del colegio Dr Modesto Chávez Franco y propuesta de intervención desde la perspectiva del trabajo social - Flores Macías, Ingrid Eugenia (2013)
The causes of pregnancy in adolescence are politically debatable, and of great emotional, social and family burden, so many factors must be examined, in addition to the obvious cause of adolescents having sex without adequate contraceptive measures.